Patients' Use of a Home-Based Virtual Reality System to Provide Rehabilitation of the Upper Limb Following Stroke. Issue 3 (1st March 2015) - Standen, Penny J.; Threapleton, Kate; Connell, Louise; Richardson, Andy; Brown, David J.; Battersby, Steven; Sutton, Catherine Jane; Platts, Fran
Abstract : Background: A low-cost virtual reality system that translates movements of the hand, fingers, and thumb into game play was designed to provide a flexible and motivating approach to increasing adherence to home-based rehabilitation. Objective: Effectiveness depends on adherence, so did patients use the intervention to the recommended level? If not, what reasons did they give? The purpose of this study was to investigate these and related questions. Design: A prospective cohort study, plus qualitative analysis of interviews, was conducted. Methods: Seventeen patients recovering from stroke recruited to the intervention arm of a feasibility trial had the equipment left in their homes for 8 weeks and were advised to use it 3 times a day for periods of no more than 20 minutes. Frequency and duration of use were automatically recorded. At the end of the intervention, participants were interviewed to determine barriers to using it in the recommended way. Results: Duration of use and how many days they used the equipment are presented for the 13 participants who successfully started the intervention. These figures were highly variable and could fall far short of our recommendations. There was a weak positive correlation between duration and baseline reported activities of daily living. Participants reported lack of familiarity with technology and competing commitments as barriers to use, although they appreciated the flexibility of the intervention and found it motivating. Limitations: The small sample size limits the conclusions that can be drawn. Conclusions: Level of use is variable and can fall far short of recommendations. Competing commitments were a barrier to use of the equipment, but participants reported that the intervention was flexible and motivating. It will not suit everyone, but some participants recorded high levels of use. Implications for practice are discussed.